A constituição profissional do professor em início de carreira: percepções dos egressos dos cursos de licenciatura da UFSCar- Sorocaba - Dessotti, Elise (Universidade Federal de São Carlos, 2017)
The present work has the objective to describe and understand the professional constitution of graduated students from teaching courses of UFSCar campus Sorocaba. The methodology is qualitative and interpretative, it has used as instruments to build the data a survey with the graduated students and semi-structured interviews with graduated students that became teachers in order to deepen the data. To understand the context of the research it has been done a documental analyses of the Political Pedagogical Project, the curricular matrixes and the general and specific curricular guidelines of each course. The first step of the building data was the application of a survey to all the graduated students of the teaching courses (Full time and nocturnal Biology, Geography, Mathematics, Chemistry and Physics) to create and analyze it has been used as categories three moments from teaching formation: initial formation, career beginning and continuous training (PACHECO; FLORES, 1999). The second step of the data building was the interviews with one graduated student from each course and to analyze were used the theoretical bases about teaching formation which involves initial and continuous training (PACHECO; FLORES, 1999; VAILLANT; MARCELO, 2012) the career beginning and its sustainability (HUBERMAN, 1997; MARCELO; VAILLANT, 2012; GUARNIERI, 2005. LIMA, 2006; HARGREAVES, 1998; FULLAN; HARGREAVES, 2000) and about professional identity (HALL, 2015; DUBAR, 2009) The main results highlighted that the graduated students feel secure about the specific contents and acknowledge that the professional constitution is a complex process, that it may gain contribution if university and school establish associations to diminish the distance from the institutions and between the theoretical-academic contents and practical. In relation to the career beginning and its sustainability the graduated students describe difficulties with the responsibilities and the conditions of the teacher work and the confrontation of the “real shock” (HUBERMAN, 1997); despite the difficulties, they keep themselves in the career because they find themselves in the students´ relationship and they like the profession. The professional identity is build along the lived experiences, but, they must deal with an identity crises (HALL, 2015) because the expectations from the scholar community are not the same as their own. They highlight the initial formation has a huge contribution to the career beginning and the professional constitution, but even bigger is the contribution from the school.
Keywords: Professor iniciante; Formação inicial; Identidade profissional docente; Constituição profissional docente; Sustentabilidade docente; Professores iniciantes; Professores - Formação; First year teachers; Teachers - In-service training; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO